Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Trade regulations drive improved global shark and ray management - Mark E. Bond; Hollie Booth; Akshay Tanna; Sarah L. Fowler; Carlos J. Polo-Silva; K.H. Stanley Shea; Floriane Cardiec; Elisabeth F. Mansur; Rima W. Jabado (Marine Policy, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Slab-failure or Slab-success? Examining the contributions of crust and mantle to post-subduction magmatism in the Ratagain Complex, NW Scotland - A. Lawrence; M. Fowler; C.G. Kingsbury; T. Knott; Darren Mark; C.T.E. Stevenson (Lithos, 2023)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

Advancing the scholarship and practice of stakeholder engagement in working landscapes: a co-produced research agenda - Weston M. Eaton; Morey Burnham; Tahnee Robertson; J. G. Arbuckle; Kathryn J. Brasier; Mark E. Burbach; Sarah P. Church; Georgia Hart-Fredeluces; Douglas Jackson-Smith; Grace Wildermuth; Katherine N. Canfield; S. Carolina Córdova; et al. (Socio-Ecological Practice Research, 2022)
Participatory approaches to science and decision making, including stakeholder engagement, are increasingly common for managing complex socio-ecological challenges in working landscapes. However, critical questions about stakeholder engagement in this space remain. These include normative, political, and ethical questions concerning who participates, who benefits and loses, what good can be accomplished, and for what, whom, and by who. First, opportunities for addressing justice, equity, diversity, and inclusion interests through engagement, while implied in key conceptual frameworks, remain underexplored in scholarly work and collaborative practice alike. A second line of inquiry relates to research–practice gaps. While both the practice of doing engagement work and scholarly research on the efficacy of engagement is on the rise, there is little concerted interplay among ‘on-the-ground’ practitioners and scholarly researchers. This means scientific research often misses or ignores insight grounded in practical and experiential knowledge, while practitioners are disconnected from potentially useful scientific research on stakeholder engagement. A third set of questions concerns gaps in empirical understanding of the efficacy of engagement processes and includes inquiry into how different engagement contexts and process features affect a range of behavioral, cognitive, and decision-making outcomes. Because of these gaps, a cohesive and actionable research agenda for stakeholder engagement research and practice in working landscapes remains elusive. In this review article, we present a co-produced research agenda for stakeholder engagement in working landscapes. The co-production process involved professionally facilitated and iterative dialogue among a diverse and international group of over 160 scholars and practitioners through a yearlong virtual workshop series. The resulting research agenda is organized under six cross-cutting themes: (1) Justice, Equity, Diversity, and Inclusion; (2) Ethics; (3) Research and Practice; (4) Context; (5) Process; and (6) Outcomes and Measurement. This research agenda identifies critical research needs and opportunities relevant for researchers, practitioners, and policymakers alike. We argue that addressing these research opportunities is necessary to advance knowledge and practice of stakeholder engagement and to support more just and effective engagement processes in working landscapes.

Habitat value of subsea wells and pipelines for fishery target species in Australia - Dianne McLean; Conrad W. Speed; Matthew Jon Birt; Jamie Colquhoun; Mark Case; Marcus Stowar; Todd Bond; Daniel Ierodiaconou; Sasha K. Whitmarsh; Michael D. Taylor; Sam Wines; David John Booth; et al. (Frontiers in Marine Science, 2022)
Subsea pipelines and wells installed to support the oil and gas industry represent some of the most extensive and numerous anthropogenic structures throughout global marine ecosystems. There remains a paucity of information on the habitat value of these structures for fishery target species and, as a result, little understanding of how decommissioning should be conducted to minimise impacts to populations of these economically and socially important species. We assess the diversity and abundance of species that are targets of recreational and commercial fisheries on 33 subsea wells and 17 pipelines across the tropical northwest and temperate southeast marine regions of Australia. We examine relationships between fish identity and abundance and a range of environmental (e.g., depth, location), infrastructure-specific (e.g., pipeline position, diameter, age, length of pipeline, height of well, position on well), and biological (% cover of epibiota) variables using video filmed by remotely operated vehicles during their routine offshore inspection and maintenance campaigns. A total of 100 fishery target species were observed across subsea well and pipeline infrastructure, 56 species uniquely observed on pipelines and nine unique to wells. The families Lutjanidae (snapper), Serranidae (rock cods, groupers, perch), and Carangidae (trevallies) were most common and abundant on both wells and pipelines. In the northwest, lutjanids were most abundant around the base of wells, in shallow depths, on shorter wells, and where pipelines spanned the seafloor. A greater number of fishery target species and abundance of ocean perch ( Helicolenus spp.) were also associated with pipelines that spanned the seafloor in temperate southeast Australia. The combined biomass of three species of snapper on wells in the northwest was 1,270 kg, with production levels for these species on each well estimated to be 105.2 g m 2 year -1 . The present study serves as an important reference point for informing decommissioning decisions for pipeline and well infrastructure and demonstrates the utility of industry-held data for science. We suggest that key predictor variables identified here be incorporated into comprehensive before-after-control-impact scientific studies for specific fields/assets to enable the prediction of potential impacts of decommissioning scenarios on marine communities present and quantification of such impacts after the decommissioning activity has occurred.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Assessment of Australian Sea Lion Bycatch Mortality in a Gillnet Fishery, and Implementation and Evaluation of an Effective Mitigation Strategy - Simon D. Goldsworthy; Brad Page; Derek J. Hamer; Andrew D. Lowther; Peter D. Shaughnessy; Mark A. Hindell; Paul Burch; Daniel P. Costa; Shannon L. Fowler; Kristian Peters; Rebecca R. McIntosh; Frederic Bailleul; et al. (Frontiers in Marine Science, 2022)
Globally, the bycatch of marine mammals in fisheries represents the greatest source of human-caused mortality that threatens the sustainability of many populations and species. The Australian sea lion ( Neophoca cinerea ) is an endangered species, whose populations off South Australia (SA) have been subject to bycatch in a demersal gillnet fishery targeting sharks since the 1960s. A comprehensive assessment was undertaken of sea lion bycatch mortality that combined independent fishery observer data with species distribution models (underpinned by satellite tracking, abundance data and population modeling) to model the relationship between at-sea foraging effort and bycatch rate. Combined with the distribution of fishing effort, these models enabled the overall level of bycatch mortality to be estimated by age, sex and subpopulation, facilitating population viability analyses that indicated most subpopulations were declining, and subject to unsustainable levels of bycatch mortality. To reduce this mortality, the Australian Fisheries Management Authority implemented an Australian Sea Lion Management Strategy that included an independent observer program (ultimately 100% electronic monitoring of gillnet fishing off SA), permanent spatial gillnet closures around all sea lion breeding sites, bycatch mortality limits that triggered temporal (18 months) spatial closures when zone-specific bycatch trigger limits were reached, and incentives for gillnet fishers to switch to an alternate fishing method (longlines). The Strategy had immediate impacts on the fishery: it resulted in significant reductions in gillnet fishing effort and on the reported bycatch of sea lions. In the next decade, there was an estimated 98% reduction in sea lion bycatch mortality from gillnet interactions and an apparent stabilization of the decline in sea lion pup abundances at some impacted breeding sites. There was an almost complete transition in the fishery from gillnets to longlines, and fishing catches returned to pre-management levels. The successful implementation of management measures to mitigate sea lion bycatch mortality in the gillnet fishery off SA was rapid, science informed, adaptive, comprehensive, and backed by strong compliance and monitoring of the fishery. It provides an important case study which demonstrates how management measures can be effectively applied to mitigate bycatch mortality of marine mammals and other marine protected species.

Invasion history shapes host transcriptomic response to a body‐snatching parasite - Zachary J. C. Tobias; Amy E. Fowler; April M. H. Blakeslee; John A. Darling; Mark E. Torchin; A. Whitman Miller; Gregory M. Ruiz; Carolyn K. Tepolt (Molecular Ecology, 2021)
By shuffling biogeographical distributions, biological invasions can both disrupt long‐standing associations between hosts and parasites and establish new ones. This creates natural experiments with which to study the ecology and evolution of host–parasite interactions. In estuaries of the Gulf of Mexico, the white‐fingered mud crab ( Rhithropanopeus harrisii ) is infected by a native parasitic barnacle, Loxothylacus panopaei (Rhizocephala), which manipulates host physiology and behaviour. In the 1960s, L . panopaei was introduced to the Chesapeake Bay and has since expanded along the southeastern Atlantic coast, while host populations in the northeast have so far been spared. We use this system to test the host's transcriptomic response to parasitic infection and investigate how this response varies with the parasite's invasion history, comparing populations representing (i) long‐term sympatry between host and parasite, (ii) new associations where the parasite has invaded during the last 60 years and (iii) naïve hosts without prior exposure. A comparison of parasitized and control crabs revealed a core response, with widespread downregulation of transcripts involved in immunity and moulting. The transcriptional response differed between hosts from the parasite's native range and where it is absent, consistent with previous observations of increased susceptibility in populations lacking exposure to the parasite. Crabs from the parasite's introduced range, where prevalence is highest, displayed the most dissimilar response, possibly reflecting immune priming. These results provide molecular evidence for parasitic manipulation of host phenotype and the role of gene regulation in mediating host–parasite interactions.

Continental‐scale acoustic telemetry and network analysis reveal new insights into stock structure - Elodie J. I. Lédée; Michelle R. Heupel; Matthew D. Taylor; Robert G. Harcourt; Fabrice R. A. Jaine; Charlie Huveneers; Vinay Udyawer; Hamish A. Campbell; Russell C. Babcock; Xavier Hoenner; Adam Barnett; Matias Braccini; et al. (Fish and Fisheries, 2021)
Delineation of population structure (i.e. stocks) is crucial to successfully manage exploited species and to address conservation concerns for threatened species. Fish migration and associated movements are key mechanisms through which discrete populations mix and are thus important determinants of population structure. Detailed information on fish migration and movements is becoming more accessible through advances in telemetry and analysis methods however such information is not yet used systematically in stock structure assessment. Here, we described how detections of acoustically tagged fish across a continental‐scale array of underwater acoustic receivers were used to assess stock structure and connectivity in seven teleost and seven shark species and compared to findings from genetic and conventional tagging. Network analysis revealed previously unknown population connections in some species, and in others bolstered support for existing stock discrimination by identifying nodes and routes important for connectivity. Species with less variability in their movements required smaller sample sizes (45–50 individuals) to reveal useful stock structure information. Our study shows the power of continental‐scale acoustic telemetry networks to detect movements among fishery jurisdictions. We highlight methodological issues that need to be considered in the design of acoustic telemetry studies for investigating stock structure and the interpretation of the resulting data. The advent of broad‐scale acoustic telemetry networks across the globe provides new avenues to understand how movement informs population structure and can lead to improved management.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Using a biophysical model to investigate connectivity between spawning grounds and nursery areas of King George whiting ( Sillaginodes punctatus : Perciformes) in South Australia’s gulfs - Troy A. Rogers; Ana Redondo Rodriguez; Anthony J. Fowler; Mark J. Doubell; Michael J. Drew; Michael A. Steer; Damian Matthews; Charles James; Bronwyn M. Gillanders (Fisheries Oceanography, 2021)
Many demersal marine fish species depend on a dispersive larval stage that connects geographically discrete sub‐populations. Understanding connectivity between these sub‐populations is necessary to determine stock structure, which identifies the appropriate spatial scale for fishery management. Such connectivity is poorly understood for King George whiting ( Sillaginodes punctatus ; Perciformes) in South Australia's gulf system, even though spawning grounds and nursery areas are adequately defined. In response to declines in commercial catches and estimated biomass, this study aimed to determine the most important spawning grounds and nursery areas to recruitment, and the connectivity between them. A biophysical model was seeded with particles according to the distribution and density of eggs throughout the spawning area in 2017 and 2018. Despite inter‐annual differences in the origins of particles, dispersal pathways and predicted settlement areas remained consistent between years. Predicted settlement was generally highest to nursery areas only short distances from regional spawning grounds, consistent with previous hydrodynamic models. However, the model also predicted that spawning in one region could contribute to recruitment in an adjacent region later in the spawning season, which aligned with the breakdown of thermohaline fronts at the entrance of each gulf. The connectivity between spawning grounds and nursery areas predicted by the model is supported by spatio‐temporal patterns in the otolith chemistry of pre‐flexion larvae and settled juveniles. Consequently, the most parsimonious explanation is that the populations of King George whiting in South Australia's gulf system constitute a single, panmictic stock, which has implications for fishery management.

Strong genetic structure in a widespread estuarine crab: A test of potential versus realized dispersal - Carolyn K. Tepolt; April M. H. Blakeslee; Amy E. Fowler; John A. Darling; Mark E. Torchin; A. Whitman Miller; Gregory M. Ruiz (Journal of Biogeography, 2020)
Aim Genetic structure has proven difficult to predict for marine and estuarine species with multi‐day pelagic larval durations, since many disperse far less than expected based on passive transport models. In such cases, the gap between potential and realized dispersal may result from larval behaviours that evolved to facilitate retention and settlement in favourable environments. Behaviour is predicted to play a particularly key role in structuring truly estuarine species, which often moderate their behaviour to remain within their natal estuaries. In such systems, this restricted dispersal may lead to high divergence, local adaptation and eventual speciation across their range. Here, we test whether a geographically widespread estuarine crab, known to have behaviour promoting larval retention, exhibits high population structure despite a 2‐ to 4‐week larval duration. Location Atlantic and Gulf Coasts of North America. Taxon White‐fingered mud crab, Rhithropanopeus harrisii . Methods Population genomic analyses across nine estuaries from New Hampshire to Louisiana using 12,638 transcriptome‐derived SNPs. Results We found highly differentiated genetic signatures among all nine estuaries, separated by 200–5,000 km of coastline. Estimates of gene flow suggest that migration is low and largely symmetrical between sites. We also observed deep phylogenetic divides corresponding to major biogeographical breaks. Main conclusions These results indicate substantial and longstanding constraints to dispersal in the species’ native range, likely arising from the emergence of geological and oceanographic barriers and sustained by behaviour that promotes estuarine retention during larval development. This work supports the idea that larval behaviour promoting estuarine retention can be reflected in substantial genetic structure even in species with multi‐week pelagic larval durations. Such behaviour‐restricted dispersal has implications for predicting adaptation and spread in estuarine species, many of which have been introduced outside their native ranges.

Enhancing the Scientific Value of Industry Remotely Operated Vehicles (ROVs) in Our Oceans - Dianne L. McLean; Miles J. G. Parsons; Andrew R. Gates; Mark C. Benfield; Todd Bond; David J. Booth; Michael Bunce; Ashley M. Fowler; Euan S. Harvey; Peter I. Macreadie; Charitha B. Pattiaratchi; Sally Rouse; et al. (Frontiers in Marine Science, 2020)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

The Significant Surface-Water Connectivity of “Geographically Isolated Wetlands” - Aram J. K. Calhoun; David M. Mushet; Laurie C. Alexander; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Stephen C. Richter; Susan C. Walls (Wetlands, 2017)

Speed breeding for multiple disease resistance in barley - Lee T. Hickey; Silvia E. Germán; Silvia A. Pereyra; Juan E. Diaz; Laura A. Ziems; Ryan A. Fowler; Greg J. Platz; Jerome D. Franckowiak; Mark J. Dieters (Euphytica, 2017)

The first field observation of intestinal eversion by a shark (broadnose sevengill, Notorynchus cepedianus) - Georgina Wiersma; Peter Verhoog; Sarah Fowler; Mark Meekan (Marine Biodiversity, 2016)

Geographically Isolated Wetlands: Rethinking a Misnomer - David M. Mushet; Aram J. K. Calhoun; Laurie C. Alexander; Matthew J. Cohen; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Susan C. Walls (Wetlands, 2015)

Foraging distribution of a tropical seabird supports Ashmole’s hypothesis of population regulation - Steffen Oppel; Annalea Beard; Derren Fox; Elizabeth Mackley; Eliza Leat; Leeann Henry; Elizabeth Clingham; Nathan Fowler; Jolene Sim; Julia Sommerfeld; Nicola Weber; Sam Weber; et al. (Behavioral Ecology and Sociobiology, 2015)

Changes in the Chlorophyll Content and Cytokinin Levels in the Top Three Leaves of New Plant Type Rice During Grain Filling - Leila Rubia; Latha Rangan; Rimjhim Roy Choudhury; Miroslav Kamínek; Petre Dobrev; Jiri Malbeck; Mark Fowler; Adrian Slater; Nigel Scott; John Bennett; Shaobing Peng; Gurdev S. Khush; et al. (Journal of Plant Growth Regulation, 2014)

Inertia in an ombrotrophic bog ecosystem in response to 9 years' realistic perturbation by wet deposition of nitrogen, separated by form - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; Sarah Leeson; Sanna Kivimaki; J. Neil Cape; Netty van Dijk; David Leaver; Mark A. Sutton; David Fowler; Leon J.L. Van den Berg; Alan Crossley; et al. (Global Change Biology, 2014)
Wet deposition of nitrogen (N) occurs in oxidized (nitrate) and reduced (ammonium) forms. Whether one form drives vegetation change more than the other is widely debated, as field evidence has been lacking. We are manipulating N form in wet deposition to an ombrotrophic bog, Whim (Scottish Borders), and here report nine years of results. Ammonium and nitrate were provided in rainwater spray as NH 4 Cl or NaNO 3 at 8, 24 or 56 kg N ha −1 yr −1 , plus a rainwater only control, via an automated system coupled to site meteorology. Detrimental N effects were observed in sensitive nonvascular plant species, with higher cumulative N loads leading to more damage at lower annual doses. Cover responses to N addition, both in relation to form and dose, were species specific and mostly dependent on N dose. Some species were generally indifferent to N form and dose, while others were dose sensitive. Calluna vulgaris showed a preference for higher N doses as ammonium N and Hypnum jutlandicum for nitrate N. However, after 9 years, the magnitude of change from wet deposited N on overall species cover is small, indicating only a slow decline in key species. Nitrogen treatment effects on soil N availability were likewise small and rarely correlated with species cover. Ammonium caused most N accumulation and damage to sensitive species at lower N loads, but toxic effects also occurred with nitrate. However, because different species respond differently to N form, setting of ecosystem level critical loads by N form is challenging. We recommend implementing the lowest value of the critical load range where communities include sensitive nonvascular plants and where ammonium dominates wet deposition chemistry. In the context of parallel assessment at the same site, N treatments for wet deposition showed overall much smaller effects than corresponding inputs of dry deposition as ammonia.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Methane emissions from soils: synthesis and analysis of a large UK data set - Peter E. Levy; Annette Burden; Mark D. A. Cooper; Kerry J. Dinsmore; Julia Drewer; Chris Evans; David Fowler; Jenny Gaiawyn; Alan Gray; Stephanie K. Jones; Timothy Jones; Niall P. McNamara; et al. (Global Change Biology, 2012)
Nearly 5000 chamber measurements of CH 4 flux were collated from 21 sites across the U nited K ingdom, covering a range of soil and vegetation types, to derive a parsimonious model that explains as much of the variability as possible, with the least input requirements. Mean fluxes ranged from −0.3 to 27.4 nmol CH 4 m −2 s −1 , with small emissions or low rates of net uptake in mineral soils (site means of −0.3 to 0.7 nmol m −2 s −1 ) and much larger emissions from organic soils (site means of −0.3 to 27.4 nmol m −2 s −1 ). Less than half of the observed variability in instantaneous fluxes could be explained by independent variables measured. The reasons for this include measurement error, stochastic processes and, probably most importantly, poor correspondence between the independent variables measured and the actual variables influencing the processes underlying methane production, transport and oxidation. When temporal variation was accounted for, and the fluxes averaged at larger spatial scales, simple models explained up to ca. 75% of the variance in CH 4 fluxes. Soil carbon, peat depth, soil moisture and pH together provided the best sub‐set of explanatory variables. However, where plant species composition data were available, this provided the highest explanatory power. Linear and nonlinear models generally fitted the data equally well, with the exception that soil moisture required a power transformation. To estimate the impact of changes in peatland water table on CH 4 emissions in the U nited K ingdom, an emission factor of +0.4 g CH 4 m −2 yr −1 per cm increase in water table height was derived from the data.

Global Competency and Issues in Contemporary Education / Agroforestry - Susan Moore; Erin Sills; Lee Allen; Douglas Frederick; Frederick Cubbage; John Garland; Julie Lydick; Gordon Holley; Jodi Roberts; Stephen Grado; Zhu Ning; Shannon Fowler; et al. (Journal of Forestry, 2011)
34We performed a five year integrated research, extension and education project aimed at strengthening global competence of students and faculty through collaboration in forestry. We sought to improve our students' ability to cooperate, increase their understanding of global dynamics of forestry markets and enhance their knowledge of various approaches to forest management and conservation with Chile as the focus. The project had four key components: (1) facilitate faculty and student involvement in Chile through Spanish language training, a website, and visits by Chilean faculty; (2) support NC State faculty and student research and study in Chile through travel grants and study tours; (3) build on faculty sabbaticals in Chile by funding student research assistants; and (4) disseminate information from Chile through multiple channels to both the university and professional communities. The faculty exchange visits; graduate student research; and participation of NCSU students, faculty and staff in the study tours to Chile had substantial effects when the participants returned to the US and disseminated information about their experiences through both formal and informal mechanisms. Both students and faculty at NCSU are more aware of forestry research, policy and management in Chile. Faculty at NCSU and Chilean universities Universidad de Concepción and Universidad de Austral have established a strong basis for collaboration and are continuing to work together on funding proposals, research, and papers. Students who participated in the study tours learned about both the culture and forestry in Chile, including similarities, differences, and lessons for the US. This presentation will describe the activities, outcomes and ongoing impacts of the project.

Dry deposition of ammonia gas drives species change faster than wet deposition of ammonium ions: evidence from a long‐term field manipulation - Lucy J. Sheppard; Ian D. Leith; Toshie Mizunuma; John Neil Cape; Alan Crossley; Sarah Leeson; Mark A. Sutton; Netty van Dijk; David Fowler (Global Change Biology, 2011)
Although the effects of atmospheric nitrogen deposition on species composition are relatively well known, the roles of the different forms of nitrogen, in particular gaseous ammonia ( NH 3 ), have not been tested in the field. Since 2002, we have manipulated the form of N deposition to an ombrotrophic bog, W him, on deep peat in southern S cotland, with low ambient N (wet + dry = 8 kg N ha −1 yr −1 ) and S (4 kg S ha −1 yr −1 ) deposition. A gradient of ammonia ( NH 3 , dry N ), from 70 kg N ha −1 yr −1 down to background, 3–4 kg N ha −1 yr −1 was generated by free air release. Wet ammonium ( NH 4 + , wet N) was provided to replicate plots in a fine rainwater spray ( NH 4 Cl at +8, +24, +56 kg N ha −1 yr −1 ). Automated treatments are coupled to meteorological conditions, in a globally unique, field experiment. Ammonia concentrations were converted to NH 3 ‐ N deposition (kg N ha −1 ) using a site/vegetation specific parameterization. Within 3 years, exposure to relatively modest deposition of NH 3 , 20–56 kg NH 3 ‐N ha −1 yr −1 led to dramatic reductions in species cover, with almost total loss of C alluna vulgaris , S phagnum capillifolium and C ladonia portentosa . These effects appear to result from direct foliar uptake and interaction with abiotic and biotic stresses, rather than via effects on the soil. Additional wet N by contrast, significantly increased C alluna cover after 5 years at the 56 kg N dose, but reduced cover of S phagnum and C ladonia . Cover reductions caused by wet N were significantly different from and much smaller than those caused by equivalent dry N doses. The effects of gaseous NH 3 described here, highlight the potential for ammonia to destroy acid heathland and peat bog ecosystems. Separating the effects of gaseous ammonia and wet ammonium deposition, for a peat bog, has significant implications for regulatory bodies and conservation agencies.

Complex modulation of L-type Ca2+ current inactivation by sorcin in isolated rabbit cardiomyocytes - Mark R. Fowler; Gianni Colotti; Emilia Chiancone; Yoshiharu Higuchi; Tim Seidler; Godfrey L. Smith (Pflügers Archiv - European Journal of Physiology, 2009)

National Threatened Species Listing Based on IUCN Criteria and Regional Guidelines: Current Status and Future Perspectives - REBECCA M. MILLER; JON PAUL RODRÍGUEZ; THERESA ANISKOWICZ‐FOWLER; CHANNA BAMBARADENIYA; RUBEN BOLES; MARK A. EATON; ULF GÄRDENFORS; VERENA KELLER; SANJAY MOLUR; SALLY WALKER; CAROLINE POLLOCK (Conservation Biology, 2007)
As countries worldwide become increasingly interested in conserving biodiversity, the profile of national threatened species lists expands and these lists become more influential in determining conservation priorities. The World Conservation Union (IUCN) Categories and Criteria for evaluating extinction risk, originally intended for use at the global level, are increasingly being used at the national level. To facilitate this process, the IUCN recently published guidelines for the application of the criteria at subglobal levels. We evaluated the application of these guidelines, focusing on the opinions and experience of the global community of national assessors. To assess the extent to which IUCN criteria have been used in official national listing efforts, we sent a survey to 180 Convention on Biological Diversity national focal points designated by governments. Of the respondents, 77% had developed national threatened species lists. Of these, 78% applied a version of the IUCN criteria, and 88% plan to produce future threatened species lists. The majority of this last group (83%) will use IUCN criteria. Of the countries that have or will develop a threatened species list, 82% incorporated their list or the IUCN criteria into national conservation strategies. We further explored the issues highlighted by the survey results by integrating the experience of assessors that have produced national lists. Most of the problems national assessors faced when applying the IUCN criteria arose when the criteria were applied at the regional level without the IUCN Regional Guidelines and when assessors were confused about the purpose of the IUCN criteria and lacked training in their proper use. To improve their clarity and increase their repeatability, we recommend that the IUCN increase communication and information exchange among countries and between regional and global assessors, potentially through an interactive Web site, to facilitate the development of national red lists and to improve their conservation value within and between countries.

Cellular distribution of calcium current is unaltered during compensated hypertrophy in the spontaneously hypertensive rat - Mark R. Fowler; Clive H. Orchard; Simon M. Harrison (Pflügers Archiv - European Journal of Physiology, 2006)

Membrane cross-talk in the early distal tubule segment of frog kidney: role of calcium stores and chloride - Gordon Cooper; Mark Fowler; Malcolm Hunter (Pflügers Archiv - European Journal of Physiology, 2001)

The intercellular adhesin locus ica is present in clinical isolates of Staphylococcus aureus from bacteremic patients with infected and uninfected prosthetic joints - Vance G. Fowler Jr; Paul D. Fey; L. Barth Reller; Anna Lisa Chamis; G. Ralph Corey; Mark E. Rupp (Medical Microbiology and Immunology, 2001)

Efficient Co-Transformation of Nicotiana Tabacum by two Independent T-DNAs, the Effect of T-DNA Size and Implications for Genetic Separation - Alex C. McCormac; Mark R. Fowler; Dong-Fang Chen; Malcolm C. Elliott (Transgenic Research, 2001)

Advances in micrometeorological methods for the measurement and interpretation of gas and particle nitrogen fluxes - David Fowler; Mhairi Coyle; Chris Flechard; Ken Hargreaves; Eiko Nemitz; Robert Storeton-West; Mark Sutton; Jan-Willem Erisman (Plant and Soil, 2001)